Tropospheric Role in the Predictability of the Surface Impact of the 2018 Sudden Stratospheric Warming Event - González-Alemán, Juan J.; Grams, Christian M.; Ayarzagüena, Blanca; Zurita-Gotor, Pablo; Domeisen, Daniela I. V.; Gómara, Iñigo; Rodríguez-Fonseca, Belén; Vitart, Frédéric (Geophysical Research Letters, 2022)
Sudden stratospheric warmings (SSWs) can have a strong impact on the troposphere. Their fingerprint is often associated with the negative phase of the Northern Annular Mode (NAM) and the North Atlantic Oscillation (NAO), and extreme weather with high societal impact. However, the mechanisms behind this downward impact are not well understood. We investigate this surface impact through its associated predictability limits, by studying the 2018 SSW event. We search for predictability barriers that occurred after the onset of the SSW and before its surface impact. It is found that dynamical tropospheric events consisting of two cyclogenesis events were the main reasons for these predictability barriers in the prediction of negative NAM/NAO anomalies reaching the surface. This work corroborates that individual synoptic events might constitute predictability barriers during the downward impact of SSW events, and thereby sheds light on stratosphere-troposphere coupling.